THE TOURISM INDUSTRY OF ETHICS AND TOURISM - Constanţa ENEA (Management & Marketing)
The tourism industry is one of the largest industries in the world, and despite recent events that have made its operating environment more complex, the industry continues to grow [Theobald, 2005, Global Tourism, 3rdedn., Butterworth-Heinemann/Elsevier]. Commensurate to the size of the industry is a growth in the number of students pursuing degree courses in tourism around the world. Despite an increasingly sophisticated literature, the relative recency of the industry and its study has meant little attention has been paid in the ethics literature to the dilemmas facing tourism managers and its students. Based on interviews with senior members of the tourism industry six scenarios are developed with pertinence to the challenges faced by industry practitioners today.